William Wordsworth’s Theoretical Contribution to Canon of Literary Criticism in Light of Preface to Lyrical Ballads - Ercüment Yaşar, (Technium Social Sciences Journal, 2020)
Wordsworth’s Preface to Lyrical Ballads, with Pastoral and Other Poems (1802) is both a revolutionary manifesto and a kind of foundational text in the context of the canon of Romantic poetry because of its normative analysis on the nature of poetry and its basic constituent parts although when compared to the systematic approaches in the twentieth century literary theory, Wordsworth does not present an autonomous critical method capable of providing universally valid principles in evaluation of the text. This paper mainly aims to discuss Wordsworth’s contribution to canon of literary criticism on the theoretical level by giving concrete examples from Preface to Lyrical Ballads, with Pastoral and Other Poems (1802) as well as scrutinizing Wordsworth’s definition of poetry and the poet, his ideas on the origin of poetry, the subject matter of poetry, and the language of poetry respectively in order to show that it is revolutionary in terms of prescribing some principles in evaluation of a literary work.